The magnetic structures of rare-earth quadruple perovskite manganites RMn7O12 - Johnson, R; Khalyavin, D; Manuel, P; Zhang, L; Yamaura, K; Belik, A (American Physical Society, 2018)
We report a neutron powder diffraction study of RMn7O12 quadruple perovskite manganites with R = La, Ce, Nd, Sm, and Eu. We show that in all measured compounds concomitant magnetic ordering of the A and B manganese sublattices occurs on cooling below the N´eel temperature. The respective magnetic structures are collinear, with one uncompensated Mn3+ moment per formula unit as observed in bulk magnetisation measurements. We show that both LaMn7O12 and NdMn7O12 undergo a second magnetic phase transition at low temperature, which introduces a canting of the B site sublattice moments that is commensurate in LaMn7O12 and incommensurate in NdMn7O12. This spin canting is consistent with a magnetic instability originating in the B site orbital order. Furthermore, NdMn7O12 displays a third magnetic phase transition at which long range ordering of the Nd sublattice modifies the periodicity of the incommensurate spin canting. Our results demonstrate a rich interplay between transition metal magnetism, orbital order, and the crystal lattice, which may be fine tuned by cation substitution and rare earth magnetism.